Society of Robotic Surgery review: recommendations regarding the risk of COVID‐19 transmission during minimally invasive surgery. (9th August 2020) - Porter, James; Blau, Elliot; Gharagozloo, Farid; Martino, Martin; Cerfolio, Robert; Duvvuri, Umamaheswar; Caceres, Aileen; Badani, Ketan; Bhayani, Sam; Collins, Justin; Coelho, Rafael; Rocco, Bernard; et al.
Abstract : Objectives: To determine the risk of COVID‐19 transmission during minimally invasive surgical (MIS) procedures Methods: Surgical society statements regarding the risk of COVID transmission during MIS procedures were reviewed. In addition, the available literature on COVID‐19 and other viral transmission in CO2 pneumoperitoneum, as well as the presence of virus in the plume created by electrocautery during MIS was reviewed. The society recommendations were compared to the available literature on the topic to create our review and recommendations to mitigate COVID‐19 transmission. Results: The recommendations promulgated by various surgical societies evolved over time as more information became available on COVID‐19 transmission. Review of the available literature on the presence of COVID‐19 in CO2 pneumoperitoneum was inconclusive. There is no clear evidence of the presence of COVID‐19 in plume created by electrocautery. Technologies to reduce CO2 pneumoperitoneum release into the operating room as well as filter viral particles are available and should reduce the exposure risk to operating room personnel. Conclusion: There is no clear evidence of COVID‐19 virus in the CO2 used during MIS procedures or in the plume created by electrocautery. Until the presence or absence of COVID‐19 viral particles has been clearly established, measures to mitigate CO2 and surgical cautery plume release into the operating room should be performed. Further study on the presence of COVID‐19 in MIS pneumoperitoneum and cautery plume is needed.